Subclinical patterns of disordered eating behaviors in the daily life of adolescents and young adults from the general population - Stephanie K. V. Peschel; Christine Sigrist; Catharina Voss; Sophia Fürtjes; Johanna Berwanger; Theresa M. Ollmann; Hanna Kische; Frank Rückert; Julian Koenig; Katja Beesdo-Baum (BMC, 2024)
Abstract Background Disordered eating behaviors (DEBs), a risk factor for the development of eating disorders (EDs), are prevalent in young people and different DEBs frequently co-occur. Previous studies on DEB-patterns have largely used traditional retrospective questionnaires to assess DEBs. In addition, most previous studies did not specifically exclude individuals with clinical EDs, which limits current knowledge concerning purely subclinical patterns of DEBs. In the present study, we aimed to explore phenotypes and group sizes of subclinical patterns of DEBs reported in everyday life via smartphone-based ecological momentary assessment (EMA) in adolescents and young adults from the general population without lifetime EDs. In secondary analyses, we further aimed to investigate whether DEB-patterns would be associated with additional previously identified risk factors for ED-development. Methods EMA was conducted in a community sample of 14-21-year-olds from Dresden, Germany, over four days for up to eight times a day and covered engagement in four DEBs: skipping eating, restrained eating, eating large amounts of food, and loss-of-control eating. Data were analyzed from N = 966 individuals without lifetime EDs with an EMA compliance rate of at least 50% (81.9% of the total sample; average compliance: 84.6%). Latent profile analyses were performed to identify subclinical patterns of DEBs, stratified by sex. Associations between symptomatic profiles and ED-risk factors were tested via regression analyses. Results Based on theoretical deliberations, statistical indices, interpretability, and parsimony, a three-profile solution, namely no DEBs, high-mixed DEBs, and low-mixed DEBs, was selected for both sexes. Both symptomatic profiles in both sexes were associated with more unfavorable manifestations in additional ED risk factors compared to the no DEBs profile, with the highest number of associations being observed in the female high-mixed profile. Conclusions The present findings suggest that problematic manifestations of DEBs in young people may occur even in the absence of an ED diagnosis and that they are associated with additional risk factors for EDs, warranting increased efforts in targeted prevention, early identification and intervention in order to counteract symptom progression.